SARS-CoV-2 variants Alpha, Beta, Delta and Omicron show a slower host cell interferon response compared to an early pandemic variant - Laine, Larissa; Skön, Marika; Väisänen, Elina; Julkunen, Ilkka; Österlund, Pamela (Frontiers in Immunology, 2022)
Since the start of the pandemic at the end of 2019, arising mutations in SARS-CoV-2 have improved its transmission and ability to circumvent the immunity induced by vaccination and previous COVID-19 infection. Studies on the effects of SARS-CoV-2 genomic mutations on replication and innate immunity will give us valuable insight into the evolution of the virus which can aid in further development of vaccines and new treatment modalities. Here we systematically analyzed the kinetics of virus replication, innate immune activation, and host cell antiviral response patterns in Alpha, Beta, Delta, Kappa, Omicron and two early pandemic SARS-CoV-2 variant-infected human lung epithelial Calu-3 cells. We observed overall comparable replication patterns for these variants with modest variations. Particularly, the sublineages of Omicron BA.1, BA.2 and a recombinant sublineage, XJ, all showed attenuated replication in Calu-3 cells compared to Alpha and Delta. Furthermore, there was relatively weak activation of primary innate immune signaling pathways, however, all variants produced enough interferons to induce the activation of STAT2 and production of interferon stimulated genes (ISGs). While interferon mRNA expression and STAT2 activation correlated with cellular viral RNA levels, ISG production did not. Although clear cut effects of specific SARS-CoV-2 genomic mutations could not be concluded, the variants of concern, including Omicron, showed a lower replication efficiency and a slower interferon response compared to an early pandemic variant in the study.